Identificação do sexo em Astronotus ocellatus: aspectos comportamentais, hormonais e moleculares - Carvalho, Aline Ferreira Souza de (2016)
This work aimed at assessing different methods to identify sex in Astronotus ocellatus considering behavioral, hormonal and molecular aspects. Thus, we ran two experiments: the first one aimed at identifying sex in adult A. ocellatus by evaluating their aggressive behavior and sexual steroid profile. Mirror test was used to assess such aggressive behavior and quantify latency, specific attacks and total attacks. Testosterone (T) and 17β-estradiol (E 2) doses, in turn, were determined by the ELISA test. We used the gold sexing standard to analyze the gonads histologically, validate the techniques proposed, and determine the stages of sex maturation. Choen‟s Kappa was used to evaluate the concordance between such sexing methods. Student‟s or Mann-Whitney‟s t tests were applied to assess likely differences in behavior and hormone profile. Identif ying sex through aggressive behavior was not possible (p=0.613 and concordance rate of 0.069). On the other hand, determining a T/E 2 ratio made it possible to identify with an 80.56% accuracy (p=0.001 and concordance rate of 0.571). We also identified significant differences (p<0.05) in T and E2 levels between male and female individuals. The second experiment aimed at assessing autosomal genes Foxl2, Sox9 and Wt1a as potential candidates for sex identification in A. ocellatus. Therefore, molecular characterization and profile determination of expression of genes Foxl2, Sox9 and Wt1a in male and female gonads were carried out. For molecular essays, we collected ovary (n=5) and testicle (n=5) fragments from adult A.ocellatus, after euthanasia. Such gonadal fragments were histologically evaluated to confirm their sex. For molecular characterization, we extracted the RNA after cDNA synthesis and amplified it in PCR with specific primers for the genes of interest. Afterwards, the DNA fragments were purified, cloned, sequenced and assessed phylogenetically. To determine the profile of gene expression, RT-qPCR essays were run. It was possible to isolate and characterize partial DNA sequences of genes Foxl2, Sox9 and Wt1a (Genbank access number: KT337395, KT337394 and KT337396, respectively). The phylogenetic analysis revealed a close relationship between the amino acid sequences in the genes of interest in A. ocellatus and other species of teleost fish. RT-qPCR essays revealed a profile of expression deeply influenced by sex, since the level of transcripts in Foxl2 (p-0.033) were significantly higher in ovaries, as opposed to testicles. On the other hand, the level of transcripts for Sox9 and Wt1a were significantly higher (p=0.020 and p=0.014) in testicles. Thus, under the conditions of these experiments, it is possible to identify sex in A. ocellatus based on sex steroid doses. Moreover, genes Foxl2, Sox9 and Wt1a may be used as possible molecular markers for sex in the species at hand.